The prediction of mental health based on variables of Self-esteem, life satisfaction and hope among College students - Tahere Rezaei; Ali Asghar Bayani; Kazem Shariatnia (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Mental health is one of the key variables in the field of Psychology and Educational Sciences that several factors have been studied in relation to it. The aim of this study is to predict students' mental health using the variables of self-esteem, life satisfaction was hope. Methods: This study was of the correlation among non-experimental studies. The population were included all students in shahrood University (9,000 student) and for the sample size used krejcie  and Morgan table and 368 were selected. A booklet that participants were asked to respond to questions, including:1-demographic Questionnaire2-General Health Goldberg and Hiller Questionnaire 3- Snyder Hope questionnaire 4- Rosenberg self esteem questionnaire.5-Diner satisfaction with life Questionnaire. To analyze the data descriptive statistics (Charts, measure of central tendency and dispersion measures) and inferential statistics (Pearson correlation coefficient, t-test and stepwise regression analysis) were used. Results: The results show that between self-esteem, satisfaction with life, hope and mental health (r=0/76 0/70 and 0/76) There is a significant correlation. Students mental health can be predicted based on variables self-esteem and (;beta =0/42), satisfaction with life (;beta = 0/21) and hope (;beta =0/52). The proportion of self-esteem variable (0/42) was more. there was no difference Between self-esteem, hope and mental health, but between life satisfaction boys scores were more than girls. Conclusion: This study showed that, in general, students with good mental health, and results showed that with increasing self-esteem, hope and life satisfaction of students can improve their mental health. Paper Type: Research Article.